Acceptance of a third COVID-19 vaccine dose, vaccine interchangeability, and clinical trial enrolment among parents of children 12–17 years in Lima, Perú - Celis, Carlos R.; Ecker, Lucie; Alvarado-Gamarra, Giancarlo; Alcalá-Marcos, Katherine; Atamari-Anahui, Noé; Balmaceda, Maria Pia; Florian, Kevin; Paredes de la Fuente, Rodrigo; Howard, Leigh M.; Grijalva, Carlos G.; Lanata, Claudio F. (Frontiers in Public Health, 2024)
Objectives To characterize factors associated with parental willingness for their children participation in a COVID-19 vaccine trial, use of different COVID-19 vaccines and acceptance of a third vaccine dose. Methods Parents of children aged 12–17 years in Lima, Perú were asked to complete an online questionnaire via social networks, from November 9, 2021, to April 23, 2022. We calculated crude and adjusted prevalence ratios with 95% confidence intervals to compare factors with the mentioned outcomes. Results From 523 parents responding, 374 completed the survey. 90.4% would give their children a third vaccine dose, 36.6% would allow their children participation in a COVID-19 vaccine clinical trial, and 33.2% would accept different vaccine brands between doses. Parental belief that COVID-19 vaccine studies met quality standards was associated with acceptance of a third booster dose (adjusted PR 3.25; 95% CI1.57–6.74; p = 0.002), enrolment in a COVID-19 clinical trial (adjusted PR 4.49; 95% CI1.25–16.06; p = 0.02), and acceptance of different COVID-19 vaccine brands between doses (adjusted PR 10.02; 95% CI1.40–71.95; p = 0.02). Conclusion Most parents would accept a third vaccine booster dose, approximately a third would participate in COVID-19 vaccine trials. Believing COVID-19 vaccines studies fulfilled quality standards was associated with the study outcomes. It is necessary to inform about the rigorous processes for the development of COVID-19 vaccines to generate confidence in parents to accept these vaccine-related outcomes.